EVALUASI IMPLEMENTASI CASES BASED LEARNING DAN DIRECT INSTRUCTION DALAM MATA KULIAH ACCOUNTING SOFTWARE “MYOB” BERDASARKAN STAKE’S COUNTENANCE MODEL - Ika Pristy Wahyuni (Universitas Sebelas Maret Surakarta, 2012)
At the higher education curriculum, especially in the department of accounting and management, accounting software courses is one of compulsory subjects that must be followed by students. Accounting software is taught to students in both semesters odd or even as a prerequisite to taking the final task. The current, accounting software courses that must be submitted to the student is MYOB (Mind Your Own Business) and accounting applications. MYOB accounting software is the most widely used worldwide.Been considered the most effective method of delivering this subject are cases based learning and direct instruction. In the implementation of cases based learning methods combined with direct instruction in accounting courses for this software, it turns out there is no more in-depth evaluation of the successful attainment of the use of this method. New evaluation of the aspects of assessing student learning outcomes in the form of formative, middle of the semester and final examination, while the overall program evaluation has not been done.This research is evaluation research by using Stake's Countenance Model that consists of three evaluation components: (1) antecedents, (2) transactions, and (3) outcomes. The research method used was case study with qualitative research. Data gathering was conducted through interview, documentation study, and observation. Decision making or judgment for each aspect or focus of evaluation was categorized into three levels: low, medium, and high. This categorization was based on the comparison of objective standard of each evaluation phase that was taken from summarized results and figured into case-order effect matrix or countenance matrix.This evaluation research resulted as follows: (1) the antecedents (input) showed that five aspects were achieved by their actualization and one aspect was not achieved, but three sub-aspects were low and one sub-aspect was moderate, (2) the transactions (process) of the seven aspects studied indicated that their the actualization was achieved but their were two low and one moderate sub-aspects, (3) the outcomes (output) revealed that two aspects were achieved and one aspect was moderately achieved in it actualization.Keyword: accounting software MYOB, cases based learning, direct instruction, stake's countenance model, antecedents, transactions, outcomes